Life cycle cost oriented seismic design optimization of steel moment frame structures with risk-taking preference - Liu, Min; Wen, Y.K.; Burns, Scott A. (Engineering structures, 2004)
Life cycle cost is considered in this paper for multiobjective design optimization of seismic steel moment-resisting frame (SMRF) structures. Initial material/construction cost and lifetime seismic damage cost, which are usually added up in the existing literature to form the total life cycle cost measure, are considered as two separate cost measures. The number of different standard steel section types is used to roughly account for the degree of design complexity related additional construction expenses. These three merit measures are subject to balanced minimization. The maximum interstory drift ratio is selected as the single seismic performance parameter for a code-compliant SMRF design and is evaluated through a static pushover analysis. Effects of randomness and uncertainty in estimating seismic demand and capacity as well as in describing seismic hazards are considered in accordance with SAC/FEMA guidelines. The lifetime seismic damage cost is then computed with designer-specified confidence level dependent percentile exceedance probabilities of prescribed drift ratio limits that demarcate a spectrum of performance levels with varied damage states. Using a multiobjective genetic algorithm, the proposed automated optimization procedure produces a set of alternative designs that exhibits optimized tradeoff among the three conflicting objectives. Therefore, designers have much freedom to choose the final structural solution with a preferred balance of initial cost and lifetime seismic damage cost while taking into due account of the degree of design complexity.